Cell-Free and Concentrated Ascites Reinfusion Therapy during Hemodialysis for Intradialytic Hypotension and Intractable Ascites. (15th October 2022) - Hayasaka, Hideyuki; Ito, Kiyonori; Ookawara, Susumu; Kofuji, Masaya; Uchida, Takayuki; Kawamura, Shunto; Gomyo, Ayumi; Miyazawa, Haruhisa; Ueda, Yuichiro; Hirai, Keiji; Kimura, Shun-ichi; Momose, Naoki; et al.
Abstract : A 60-year-old woman with POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes) syndrome and intractable ascites presented with acute renal failure and received hemodialysis (HD) therapy. Due to frequent intradialytic hypotension, ultrafiltration with cell-free and concentrated ascites reinfusion therapy (CART) was performed to adequately manage the body fluid status and massive ascites. During HD with CART, her blood pressure was maintained compared with that during HD without CART, and an ultrafiltration volume of 3.7 L was achieved after HD with CART. In HD patients with intradialytic hypotension and massive ascites, the combination of CART and ultrafiltration during HD may be an effective therapeutic option for body-fluid management.